Risk Factors and Outcomes for Postoperative Ileus After Small Intestinal Fistula Excision in Patients With Diffuse Extensive Abdominal Adhesions - Tian, Weiliang; Yan, Ming; Xu, Xin; Yao, Zheng; Zhao, Risheng (Frontiers in Surgery, 2021)
Purpose: The study aimed to investigate the risk factors for postoperative ileus (POI) after small intestinal fistula excision (SIFE) in patients with diffuse extensive abdominal adhesions. Methods: From October 2010 to December 2019, we enrolled patients who underwent SIFE and had diffuse extensive abdominal adhesions. Patients were divided into the POI group and the non-POI group according to its occurrence. We then investigated and analyzed the clinical characteristics of both groups. Result: A total of 247 patients were enrolled into the study. There were 100 patients in the POI group, and 147 patients in the non-POI group. A multi-variable logistic regression analysis revealed that blood loss during SIFE (OR = 1.001; 95% CI: 1.000-1.259; P = 0.012), postoperative lactate(OR = 1.212; 95% CI: 1.001–1.304; P = 0.015), grade V abdominal adhesions (OR = 2.518; 95% CI: 1.814-3.44; P = 0.024), and time for recovery of lactate <2 mmol/L (OR = 2.079; 95% CI: 1.599-3.616; P =0.026) were associated with POI. Moreover, POI was also associated with prolonged postoperative stay in the hospital (HR = 3.291; 95% CI: 2.511–4.172; P = 0.014). Conclusion: Blood loss during operation, grade V abdominal adhesions, positive fluid balance within 48 hours of operation, and time for recovery of lactate were the risk factors for POI after SIFE in patients with diffuse extensive abdominal adhesions.